USING MOBILE APPLICATION TO PROMOTE AUTONOMOUS LEARNING FOR SYNTAX SUBJECT - Tuti Purwati (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2018)
This is a descriptive qualitative research aiming at exploring the use of mobile apps to promote autonomous learning for students of English Education study program in Syntax subject. Syntax is given in the fourth semester and the lesson objective is students are able to analyze sentence construction in their correct structures. There are three mobile apps used namely Quizlet, Socrative, and Sli.do. They are used randomly based on certain subtopic in the semester. Purposive sampling is applied for data collection. The data are then analyzed using content based analysis. It is found out that the use of mobile apps is able to promote students’ autonomous learning since they are eager to dig more and learn further to find materials for their subject namely Syntax. They are challenged to find answers to some problems given by the lecturer. They become more creative in presenting ideas as well as doing tree diagram analysis on sentence constructions.